2019
DOI: 10.13057/biodiv/d201209
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: First record of Arapaima gigas (Schinz, 1822) (Teleostei: Osteoglossomorpha), in the Brantas River, Sidoarjo, East Java, Indonesia

Abstract: Abstract. Fadjar M, Islamy RA, Herawati EY. 2019. Short communication: First record of Arapaima gigas (Schinz, 1822) (Teleostei: Osteoglossomorpha), in the Brantas River, Sidoarjo, East Java, Indonesia. Biodiversitas 20: 3527-3531. The arapaima (= Arapaima gigas) is the largest freshwater fish in the Neotropical region, obligate air-breathing fish that known to reach up to 3 m - 3.90 m in length and 200 kg in weight endemic to the Amazon basin. Arapaima gigas is giant osteoglossomorph and obligate air‐breathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Further research, we suggest to applicate this method to other native or non-native fish that appear in Indonesian waters, such as Arapaima (Fadjar et al, 2019), Aligator gar (Hasan et al, 2020), Channidae (Pratama et al, 2020), Gobiidae (Hasan et al, 2021), Cichlidae (Insani et al, 2020), and Cyprinidae (Hasan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Further research, we suggest to applicate this method to other native or non-native fish that appear in Indonesian waters, such as Arapaima (Fadjar et al, 2019), Aligator gar (Hasan et al, 2020), Channidae (Pratama et al, 2020), Gobiidae (Hasan et al, 2021), Cichlidae (Insani et al, 2020), and Cyprinidae (Hasan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Mexico have reported C. urophthalmus as host to a diverse assortment of parasites, including 71 different helminth species (Salgado-Maldonado 2006) and a tapeworm of the genus Bothriocephalus. Further researchers need to reobserve this population of fish in both adult and juvenile phases (Fadjar et al, 2019). Besides, measurements of sexual dimorphism are also required to analyze the females' ratio in the reservoir (Pramono et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cichlidaeis a wellknown spread and invadesworldwide (Insani et al, 2020;Hasan et al, 2020a;2020b). The spread of invasive species will decrease the biodiversity of native fish that resulted in what is termed biotic homogenization and is a worldwide phenomenon (Hasan and Tamam, 2019;Fadjar et al, 2019;Islamy and Hasan, 2020). The ornamental fish trade, nutritional needsand recreational fishingis a crucial pathway for the occurrence of alien fishes from disparate regions (Bijukumar et al, 2015;Pratama et al, 2019;Serdiati et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, industrialization, like other human activities that impact on the environment, often results in pollution and degradation (Poddar & Sahu 2015). The pollution will decrease aquatic biodiversity although not impacted to non-native invasion fish such as arapaima and alligator gar (Fadjar et al 2019;Hasan et al 2020). Wastewater from sugar industries is one that has complex characteristics and is considered a challenge for environmental engineers in terms of treatment as well as utilization (Poddar & Sahu 2015).…”
Section: Introductionmentioning
confidence: 99%